EXPLORING NATURE OF WORK FAMILY CONFLICT: AN EXPLORATORY STUDY IN THE BANKING SECTOR - Kengatharan, N. (University of Jaffna, 2016)
The work family literature demonstrates the great vitality and diversity of scholarship and it is an omnipresent factor in the study of contemporary organizations and society. This study was designed to diagnose the pervading nature of work family conflict in Sri Lanka. A total of fifteen respondents were purposively selected from a high status occupations viz., banking organisations and the experience survey was employed. The majority of the employees interviewed are in accord with existence of time based and strain based work family conflict in Sri Lanka. Nonetheless, as the third form of work family conflict-behaviour based work family conflict- in the vantage point of the majority of the employees opined that there was a flimsy of evidence to its existence. Most importantly, this study identified a new form of psychological based work family conflict and thus these novel insights unequivocally contribute to revamp the work family conflict literature. This study becomes a springboard for future research studies.
Keywords: High status occupation; Role theory; Work family conflict